Bacterial Communities in the Rhizosphere of Amilaceous Maize (Zea mays L.) as Assessed by Pyrosequencing - Correa-Galeote, David; Bedmar, Eulogio J.; Fernández-González, Antonio J.; Fernández-López, Manuel; Arone, Gregorio J. (Frontiers in Plant Science, 2016)
Maize (Zea mays L.) is the staple diet of the native peasants in the Quechua region of the Peruvian Andes who continue growing it in small plots called chacras following ancestral traditions. The abundance and structure of bacterial communities associated with the roots of amilaceous maize has not been studied in Andean chacras. Accordingly, the main objective of this study was to describe the rhizospheric bacterial diversity of amilaceous maize grown either in the presence or the absence of bur clover cultivated in soils from the Quechua maize belt. Three 16S rRNA gene libraries, one corresponding to sequences of bacteria from bulk soil of a chacra maintained under fallow conditions, the second from the rhizosphere of maize-cultivated soils, and the third prepared from rhizospheric soil of maize cultivated in intercropping with bur clover were examined using pyrosequencing tags spanning the V4 and V5 hypervariable regions of the gene. A total of 26031 sequences were found that grouped into 5955 distinct operational taxonomic units which distributed in 309 genera. The numbers of OTUs in the libraries from the maize-cultivated soils were significantly higher than those found in the libraries from bulk soil. One hundred ninety seven genera were found in the bulk soil library and 234 and 203 were in those from the maize and maize/bur clover-cultivated soils. Sixteen out of the 309 genera had a relative abundance higher than 0.5% and the were (in decreasing order of abundance) Gp4, Gp6, Flavobacterium, Subdivision3 genera incertae sedis of the Verrucomicrobia phylum, Gemmatimonas, Dechloromonas, Ohtaekwangia, Rhodoferax, Gaiella, Opitutus, Gp7, Spartobacteria genera incertae sedis, Terrimonas, Gp5, Steroidobacter and Parcubacteria genera incertae sedis. Genera Gp4 and Gp6 of the Acidobacteria, Gemmatimonas and Rhodoferax were the most abundant in bulk soil, whereas Flavobacterium, Dechloromonas and Ohtaekwangia were the main genera in the rhizosphere of maize intercropped with bur clover, and Gp4, Subdivision3 genera incertae sedis of phylum Verrucomicrobia, Gp6 and Rhodoferax were the main genera in the rhizosphere of maize plants. Taken together, our results suggest that bur clover produces specific changes in rhizospheric bacterial diversity of amilaceous maize plants.